Faktor – Faktor Yang Mempengaruhi Kepuasan Pelanggan Kartu Telkomsel Di Kecamatan Medan Baru - Tania Syahputri Siregar; Adelina Lubis (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2022)
The purpose of this research is to see and analyze the influence of service quality, product quality, price, promotion. The research method used is associative research, where variables are measured by a Likert scale. The test method is done by a list of questions (questionnaire) and observation (observation). The population of this research is all consumers of Medan Baru Subdistrict, Merdeka Village, which can be 100 people. Withdrawal of samples using the Slovin method or what is known as the Slovin formula. In this study, the sample size was 50 people. Data processing or analysis using SPSS software version 21, with descriptive analysis and testing multiple regression analysis. The results showed that : (1) Partially the variable of customer satisfaction service quality in Medan Baru District. (2) Partially the product quality variable affects customer satisfaction in Medan Baru District. (3) Partially the price variable affects customer satisfaction in Medan Baru District. (4) Partially the promotion variable affects customer satisfaction in Medan Baru District. (5) Simultaneously there is a positive and significant influence between the variables of service quality, product quality, price, promotion affecting customer satisfaction in Medan Baru District.